Implementasi Program Pembinaan Kemandirian Dan Kerohanian Pada Narapidana Narkotika Di Lembaga Pemasyarakatan Kelas IIb Lamongan - Mahmud Aprian Mabruri; Alif Firdaus Zamzam; Midkholus Surur; Eva Nur Laily Rohmah; Sri Handayawati (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study examines the implementation of the Independence and Spirituality Development Program for narcotics prisoners at the Class IIB Lamongan Penitentiary. The purpose of this study is to determine how the implementation of the development program is and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a descriptive method, by describing the results of the study and analyzing them so that the results are obtained and then concluding them. This study uses data sources from scientific journals, book literature, and websites. The results of the study indicate that the service of the Independence and Spirituality Development program can be said to be in accordance with the criteria of George Edward III's theory, namely communication, resources, disposition, and bureaucratic structure. So that it obtains the results that the Independence and Spirituality Development Program in the Class IIB Lamongan Penitentiary is quite effective, the implementation carried out is beneficial for WBP who participate in the Independence and Spirituality Development Program. However, there are several obstacles faced, such as limited human resources, facilities, budget, and motivation of prisoners and social stigma from the community. This study concludes that the independence and spirituality development program in the Class IIB Lamongan Penitentiary has a positive impact on prisoners, but it needs to be improved in certain aspects to ensure the sustainability and effectiveness of the program in the future.